Bevacizumab as First-Line Treatment in HER2-Negative Advanced Breast Cancer: Pros and Cons. Issue 5 (September 2016) - Sini, Valentina; Cassano, Alessandra; Corsi, Domenico; De Laurentiis, Michele; Gamucci, Teresa; Mauri, Mariella; Naso, Giuseppe; Roselli, Mario; Maria Ruggeri, Enzo; Tonini, Giuseppe; Vici, Patrizia; Zampa, Germano; et al.
Purpose: Bevacizumab, a humanized, anti-vascular endothelial growth factor-A monoclonal antibody, has shown efficacy in a number of cancers. However, its use in metastatic breast cancer (MBC) remains controversial. Methods: A literature review using the PubMed database was performed to update the currently available clinical trials evidence on bevacizumab in the first-line treatment of breast cancer. In addition, the proceedings of selected oncology annual meetings were searched for relevant presentations. Results: This article reviews the available evidence for bevacizumab as first-line therapy for MBC and discusses its current and future applicability in the management of MBC. Three phase III trials (ECOG-2100, AVADO, RIBBON-1) demonstrated that the addition of bevacizumab to chemotherapy is well-tolerated and improves progression-free survival and objective response rates in the first-line setting. These findings were supported by a large clinical practice-based study (ATHENA) and a recent clinical trial in which bevacizumab added to paclitaxel showed notable activity in triple-negative MBC. However, bevacizumab has thus far not demonstrated a significant benefit in overall survival. Conclusions: The addition of bevacizumab to chemotherapy is well-tolerated and produces substantial improvements in overall response rate and progression-free survival, compared with chemotherapy alone, in advanced HER2-negative breast cancer. Nevertheless, it has thus far not demonstrated a significant benefit in overall survival. Whether prolongation of progression-free survival is enough to consider bevacizumab efficacious is unclear. Based on the available clinical trials results, bevacizumab is a part of the complex therapeutic strategy of advanced HER2-negative breast cancer.